Anima: Modular Workflow System for Comprehensive Image Data Analysis - Rantanen, Ville; Valori, Miko; Hautaniemi, Sampsa (Frontiers in Bioengineering and Biotechnology, 2014)
Modern microscopes produce vast amounts of image data, and computational methods are needed to analyze and interpret these data. Furthermore, a single image analysis project may require tens or hundreds of analysis steps starting from data import and preprocessing to segmentation and statistical analysis; and ending with visualization and reporting. To manage such large-scale image data analysis projects, we present here a modular workflow system called Anima. Anima is designed for comprehensive and efficient image data analysis, and it contains several features that are crucial in high-throughput image data analysis: programming language independence, batch processing, easily customized data processing, interoperability with other software via application programming interfaces, and advanced multivariate statistical analysis. The utility of Anima is shown with two case studies focusing on testing different algorithms developed in different imaging platforms and an automated prediction of alive/dead C. elegans worms by integrating several analysis environmens. Anima is fully open source and available with documentation at http://www.anduril.org/anima